Bulletin 66 Tests of Permissible Explosives - Clarence Hall; Spencer P. Howell (The National Institute for Occupational Safety and Health (NIOSH), 1913)
The tests and studies begun by the United States Geological Survey in the fall of 1908 with a view to lessening the accidents attending the use of explosives in coal mining are being continued by the Bureau of Mines at the Pittsburgh experiment station and in the field. One hundred and six applications for the testing of 209 different explo- sives had been received at the Pittsburgh station prior to March 1, 1913, and on that date 97 explosives that had passed the required tests were on the "permissible" list issued by the bureau. This bul- letin gives the results of tests of all permissible explosives tested between May 15, 1909, and March 1, 1913. Bulletin 15 entitled "Investigations of Explosives used in Coal Mines" contains the results of tests of 17 permissible explosives tested prior to May 15, 1909. A copy of the test requirements and the names of explosives on the per- missible list dated March 1, 1913, are appended to this bulletin. An explosive is considered permissible for use in coal mines when it is similar in all respects to the sample that passed the tests required by the bureau, and when it is used in accordance with the conditions prescribed. The physical tests reported in this bulletin were conducted by Messrs. H. F. Braddock, A. J. Strane, J. W. Koster, A. S. Crossfield, A. J. Hazlewood, A. B. Coates, and J. E. Tiffany at the Pittsburgh experiment station of the bureau. The act of Congress making appropriations for sundry civil ex- penses of the Government for the fiscal year ending June 30, 1912, authorized the Secretary of the Interior to charge a fee covering the actual necessary expenses involved in making such tests by the Bureau of Mines as might be approved by him. After careful consideration had been given to the actual necessary expenses involved in the test- ing of explosives to determine their permissibility for use in coal mines, the sum of $150 was approved by the Secretary of the Interior as a reasonable charge for each complete official test. During the first year this law was in effect the fees collected amounted to more than $6,000.